Introducción a las microcomputadoras - Cordero Borboa, Luis; Guzmán Arenas, Adolfo; Torres Fentanes, José Armando; Portilla Robertson, Marcial; Ríos Zertuche Ortuño, Daniel (My University, 1980)
This book has two major objetives: to teach procedures for the design of software systems and to provide a basis for judgement in the design of software. To facilitate our task, we have taken specific example from system programs. We discuss the design and implementation of the major systems components. What is systems programming? You may visualize a computer a some sort of beast that obeys all commands, it has been said that computers are basically people made out of metal or, conversely, people and computers made out of flesh and blood. However, once we get close to cumputers, we see that they are basically machines that follow very specific and primitive instructions.
Keywords: arquitectura; minicomputadora; direccionamiento; conjunto; aplicaciones